(untitled) (Research, Society and Development, 2022)
Introduction: The nutritionist plays a substantial role in palliative care in the lives of cancer patients and their families. As a member of the multidisciplinary team, she works to reduce and control symptoms and improve patients’ quality of life. Methodology: A bibliographic narrative review was carried out in the analysis of books, articles and the National Cancer Institute (INCA), in the period between 2012 and 2022. The keywords were used for the composition of the search: Oncology, Nutrition, Palliative Care and Food. Results and Discussion: The results showed an important reduction in the side effects caused by the treatment, providing nutritional guidelines relevant to these individuals. In this final phase, food also plays an important role, focusing on promoting relief from suffering and quality of life. Conclusion: In addition to providing clarification and guidance in order to prolong survival, the nutritionist must guide the patient and their families about the Nutritional Therapy in use, considering their wishes without considering their clinical conditions and ethical aspects.